Chloride Ion‐Containing Polymeric Ionic Liquids for Application as Electrolytes in Solid‐State Batteries. Issue 1 (27th November 2022) - Ehrlich, Lisa; Pospiech, Doris; Muza, Upenyu L.; Lederer, Albena; Muche, Julia; Fischer, Dieter; Uhlmann, Petra; Tzschöckell, Felix; Muench, Simon; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Organic, solid‐state batteries require efficient solid electrolytes able to provide stable ion conduction. Here, solid electrolytes based on ionic liquid (IL) polymers with chloride counterions as electrolyte materials for batteries are presented. Acrylic monomers with imidazolium substituents with alkyl side groups that are linked by alkyl spacers to the acrylic group are employed. The IL monomers with chloride counterions are either converted by thermally initiated radical polymerization into linear homopolymers or incorporated into polymer networks by UV‐initiated copolymerization utilizing a bifunctional, non‐ionic cross‐linker. Both procedures successfully yielded the desired materials, which is confirmed by NMR spectroscopy (linear homopolymers) or Raman spectroscopy (IL networks). The ionic conductivities at room temperature are measured by Electrochemical Impedance Spectroscopy. The ionic conductivities of the linear homopolymers are in the range of 10 −4 to 10 −6 S cm −1, while those of the IL networks are about two orders of magnitude lower. They increase to 10 −4 S cm −1 at 70 °C. The electrochemical stability is examined by Linear Sweep Voltammetry and is proven in the voltage range of −2 to +2 V. The results reveal that the materials represent promising electrolytes for potential solid‐state battery applications. Abstract : Acrylic ionic liquid monomers are synthesized and employed for the preparation of linear homopolymers and polymer networks intended for application as chloride‐containing polymer electrolytes in organic solid‐state batteries. It is demonstrated that their ionic conductivities with respect to the chloride ions, thermal, and electrochemical stabilities meet the requirements for batteries.